IMAGE STATES AND THE PROPER WORK FUNCTION FOR A SINGLE LAYER OF NA AND K ON CU(111), CO(0001), AND FE(110) - Fauster, Thomas; et al. (Physical Review B, 1993)
High-resolution photoemission and two-photon photoemission spectroscopy have been used for a comparative study of the electronic structure of a single layer of Na and K on Cu(111), Co(0001), and Fe(110). All systems under investigation exhibit an occupied alkali-induced state near the Fermi energy as well as a series of unoccupied states converging toward the vacuum energy, which are identified as image-potential states. For Na (K) on any of the substrates we find the lowest image state to be located at an energy of 2.04+/-0.03 eV (1.62+/-0.03 eV) above the Fermi level. From this and from the convergence behavior of the image-state series we conclude that the work function for the perfect single alkali layer is independent of the substrates investigated, and is characteristic for the alkali metal. This is in contrast to results of conventional work-function measurements, but in accordance with the theoretical expectation.